An empirical study on customers’ satisfaction level regarding digital products of Al-Arafah Islami Bank Limited - Ridwan, Mashrur (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2016.